The concept of creative economy development-strengthening post COVID-19 pandemic in Indonesia: Strategy and public policy management study - Chollisni, Atiqi; Syahrani, Syahrani; Dewi, Sandra; Utama, Andrew Shandy; Anas, M. (Linguistics and Culture Review, 2022)
This study aims to determine the concept of creative economy development in Indonesia after the COVID-19 pandemic based on management strategies, policies, and the role of other economic actors. This research is a survey research based on ethnography. It is called ethnography because researchers will conduct survey activities in the field by taking several creative economic actors in Indonesia as samples. Based on the research results, it turns out that there are several strategies and policies that can be taken by several parties, both local governments, economic actors, economic activists/observers, and the general public. Thus, the creative economy in Indonesia will continue to survive and be developed to maintain the integrity of the welfare of the Indonesian people after the COVID-19 pandemic. Because it is the source of community life.